Application of Taguchi method for optimization of concrete strengthened with polymer after high temperature - Tanyildizi, Harun; Sahin, Murat (Elsevier Sci Ltd, 2015)
In this study, the importance of experimental parameters on the compressive strength and ultrasonic pulse velocity of the concrete strengthened with polymer after exposure to high temperature was investigated statistically. The thirty-two experiments were conducted according to the L-32 (2(1) x 4(9)) array proposed by the Taguchi method. The main parameters of experiments were selected as the polymerization type, the percentage of silica fume, and heating degree. After the specimens were exposed to temperatures of 20 degrees C, 200 degrees C, 400 degrees C and 600 degrees C, the specimens were allowed to stand in the monomer with 1% Benzoyl peroxide for 24 h under atmospheric conditions. They were carried out the polymerization at 60 degrees C for 3 h. They were applied the ultrasonic pulse velocity and compressive strength tests. The significance levels of the experimental parameters, which indicate how the factors affect the compressive strength and ultrasonic pulse velocity, were determined by using variance (Anova) method. The Taguchi results showed that the maximum ultrasonic pulse velocity and compressive strength of concrete was obtained from the concrete strengthened with polymer containing 5% silica fume admixture exposed to 200 degrees C. The anova results showed that the silica fume percentage was the most significant effect on the compressive strength and ultrasonic pulse velocity. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Concrete; Polymerization; Taguchi method; High temperature; Compressive strength; Ultrasonic pulse velocity